Il WebGis sugli tsunami: un utile strumento di consultazione - Fago, Paola; Venerito, Maria; Piscitelli, Arcangelo; Pignatelli, Cosimo; Milella, Maurilio; Sansò, Paolo; Mastronuzzi, Giuseppe (GEOmedia, 2013)
The need to cr eate an integrated maritime policy underline by the European Commission has been taken on board in Italy through the achievement of the Program RITMA RE, the Italian Researc h for the Sea. Concerning of this project, has been drafted a list of scientific references about tsunami events that occ urr ed in Italy. The articles have been collected through the consultation of digital libraries; arr anged by area of study and inserted into a geographic database. This geo-database has been used for GIS implementation, subsequently published on the web, via map serv er, on the site of the program Ritmare (www.ritmare.it).